The Big BAM Theory: An Open and Closed Case? - Wu, Runrun (Biochim Biophys Acta Biomembr, 2019)
The β-barrel assembly machinery (BAM) is responsible for the biogenesis of outer membrane proteins (OMPs) into the outer membranes of Gram-negative bacteria. These OMPs have a membrane-embedded domain consisting of a β-barrel fold which can vary from 8–36 β-strands, with each serving a diverse role in the cell such as nutrient uptake and virulence. BAM was first identified nearly two decades ago, but only recently has the molecular structure of the full complex been reported. Together with many years of functional characterization, we have a significantly clearer depiction of BAM’s structure, the intra-complex interactions, conformational changes that BAM may undergo during OMP biogenesis, and the role chaperones may play. But still, despite advances over the past two decades, the mechanism for BAM-mediated OMP biogenesis remains elusive. Over the years, several theories have been proposed that have varying degrees of support from the literature, but none has of yet been conclusive enough to be widely accepted as the sole mechanism. We will present a brief history of BAM, the recent work on the structures of BAM, and a critical analysis of the current theories for how it may function.